Identication of clays and iron oxides in the sugar cane plantations of Pomalca distric's - Cerón, María (2021)
We have identied the presence of Fe oxides, clays and other minerals in the clay fractions of six samples gathered at three pits practiced in soils of sugar cane plantations of the agroindustrial company Pomalca S.A.A. These plantations are located in the District of Pomalca, Province of Chiclayo, Lambayeque Region, Peru. The pits were identied as: Estrella, Estreno and Mochica. The X-ray diractometry and transmission Mössbauer spectroscopy techniques, complemented with routine physical-chemical analyses, allowed us to obtain results that resolved the identication of the structural and mineralogi- cal phases of the iron oxides present which were assigned to hematite, as well as Fe2+ sites located in the structure of clays minerals such as Illite and/or montmorillonite, and a Fe3+ site assigned to the structure of kaolinite.